Unraveling the Association: How Identity Mediates the Impact of Childhood Trauma on Criminal Behavior - Stefan Bogaerts; Deni Tressová; Esmée Feijen; Marija Janković (Behavioral Sciences)
Previous research has consistently linked childhood trauma to criminal behavior in adulthood, yet the mechanisms driving this association remain poorly understood. This study investigated whether identity mediates this relationship, focusing on three identity constructs: consolidated identity, disturbed identity, and lack of identity. Criminal behavior was operationalized as a dichotomous variable, distinguishing between 103 community participants (53.9%) and 88 forensic psychiatric patients (46.1%) in a sample of 191 male participants (Mage = 39.82, SDage = 14.14). Mediation analysis was conducted using PROCESS macro model 4, controlling for age and overall personality dysfunction. The results demonstrated that childhood trauma was associated with adult criminal behavior. Additionally, childhood trauma was positively associated with lack of identity but showed no significant effect on consolidated and disturbed identity. Likewise, lack of identity was the only identity variable associated with criminal behavior and emerged as the sole mediator between childhood trauma and criminal behavior. These findings underscore the important role of identity, particularly the lack of identity, in understanding pathways to criminal behavior. Interventions aimed at strengthening individuals’ sense of self may help mitigate criminal tendencies in individuals with a history of childhood trauma, though longitudinal research is needed to further validate these findings.